2006
DOI: 10.1177/039463200601900417
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies in Patients with Cancer

Abstract: Antiphospholipid antibodies are generally associated with Antiphospholipid Syndrome, which can occur as a primary disorder or may be secondary to connective tissue disease or tumour. The presence of antiphospholipid antibodies in patients with tumour disease is responsible for thrombotic complications. In a population of 53 tumor patients with positive carcinoembryonic antigen CEA, carbohydrate antigen CA19.9, CA125 and CA15.3 markers, IgM and IgG anticardiolipin and antiphosphatidylinositol were detected by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Some reports have also demonstrated an association between gastrointestinal cancers, such as gastric signet ring cell adenocarcinoma and aPL [5]. A previous study showed that moderate-to-high levels of antiphospholipid antibodies were present in a sample of 53 patients with positive CEA and CA19-9 tumor markers, suggesting a possible association with gastrointestinal tumors [6]. Here, we report the rare case of a patient with APS in the presence of invasive adenocarcinoma of the rectosigmoid colon.…”
Section: Introductionmentioning
confidence: 51%
“…Some reports have also demonstrated an association between gastrointestinal cancers, such as gastric signet ring cell adenocarcinoma and aPL [5]. A previous study showed that moderate-to-high levels of antiphospholipid antibodies were present in a sample of 53 patients with positive CEA and CA19-9 tumor markers, suggesting a possible association with gastrointestinal tumors [6]. Here, we report the rare case of a patient with APS in the presence of invasive adenocarcinoma of the rectosigmoid colon.…”
Section: Introductionmentioning
confidence: 51%
“…IgA-IgG-and IgM-aCL were done by kits for Elisa test (Alfa Wassermann, Alanno, Pescara, Italy) as previously reported [20] and have been repeated three times; similar results were obtained.…”
Section: Iga- Igm- and Igg-acl Evaluation Measurements Ofmentioning
confidence: 65%
“…The presence of these antibodies in the diagnosis of tumor disease is correlated with high risk of developing thrombotic complications [19] which represent a significant cause of morbidity and mortality in cancer patients. Interestingly, it is has been highlighted that high levels of IgM and IgG aCL antibodies are produced only in the patients affected with gastroenteric tumor that have high level of CA19.9+ and CEA-CA19.9+, and not in patients with ovary and breast tumor [20]. So far there are no data regarding the possible role and production of IgA aCL in the patients with gastroenteric tumor, especially for the role of IgA immunization in the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers can be either fluid or tissue‐based molecules that along with other diagnostic approaches may increase the precision of a correct diagnosis. In humans, several serum tumour markers have been detected including prostate serum antigen, 9 carcinoembryogenic antigen, 10 different carbohydrate antigen (CA) 125, CA19.9, CA15.3, 11–13 α ‐fetoprotein, 14 human chorionic gonadotro‐phin 15 and lactate dehydrogenase (LDH) 15 . Unfortunately, none of the markers are specific for cancer or pathognomic for a specific disease but they may act as important supplementary tests with more conventional diagnostics.…”
Section: Introductionmentioning
confidence: 99%